Structural, optical and photo-catalytic activity of nanocrystalline NiO thin films. (March 2016) - Al-Ghamdi, Attieh A.; Abdel-wahab, M. Sh.; Farghali, A.A.; Hasan, P.M.Z.
Graphical abstract: Highlights: Synthesis of nanocrystalline NiO thin films with different thicknesses using DC magnetron sputtering technique. Effect of film thickness and particle size on photo-catalytic degradation of methyl green dye under UV light was studied. The deposited NiO thin films are efficient, stable and possess high photo-catalytic activity upon reuse. Abstract: Physical deposition of nanocrystalline nickel oxide (NiO) thin films with different thickness 30, 50 and 80 nm have been done on glass substrate by DC magnetron sputtering technique and varying the deposition time from 600, 900 to 1200 s. The results of surface morphology and optical characterization of these films obtained using different characterization techniques such as X-ray diffraction (XRD), field emission scanning electron microscope (FESEM), photoluminescence (PL) and UV–vis spectrophotometry provide important information like formation of distinct nanostructures in different films and its effect on their optical band gap which has decreased from 3.74 to 3.37 eV as the film thickness increases. Most importantly these films have shown very high stability and a specialty to be recycled without much loss of their photo-catalytic activity, when tested as photo-catalysts for the degradation of methyl green dye (MG) from the wastewater under the exposure of 18 W energy of UV lamp.